Toll-Like Receptors in the Pathogenesis of Alcoholic Liver Disease. (3rd August 2010) - Petrasek, Jan; Mandrekar, Pranoti; Szabo, Gyongyi
Abstract : In the multifactorial pathophysiology of alcoholic liver disease (ALD), inflammatory cascade activation plays a central role. Recent studies demonstrated that Toll-like Receptors, the sensors of microbial and endogenous danger signals, are expressed and activated in innate immune cells as well as in parenchymal cells in the liver and thereby contribute to ALD. In this paper, we discuss the importance of gut-derived endotoxin and its recognition by TLR4. The significance of TLR-induced intracellular signaling pathways and cytokine production as well as the contribution of reactive oxygen radicals is evaluated. The contribution of TLR signaling to induction of liver fibrosis and hepatocellular cancer is reviewed in the context of alcohol-induced liver disease.